Quality Control of Frozen Fish Based on Fault Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA) Methods - Aryana Dwi Septania; Leli Deswindi (International Journal of Education, Information Technology, and Others, 2022)
This research conduct in frozen fish supplier based in east Java, Indonesia, namely Biji Sesawi company. Focuses on the issue of improves the quality of frozen fish stored in the Cold Storage. The research method is based on a qualitative research by conducting interviews with quality control and machine operators to analyze historical data from September to November 2021 using Fault Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA) tools. The results showed that the dominant type of defect was the change in the surface of the yellow fish with a defect percentage of 21.99% of the 7 types of defects that occurred in frozen fish in accordance with the characteristics determined by the Ministry of Marine Affairs and Fisheries (KKP) of Republic Indonesia. Based on Fault Tree Analysis (FTA), the factors that cause the surface of the fish to change into yellow in the frozen are the inaccurate application of the FIFO system and the room temperature level. The suggestions to improve the quality of stored fish are to maintain the distance of new products placed in Cold Storage carried out by the maintenance department, which aims to make it easier for employees to take products that are difficult to reach and the duration of products stored. The final results of the research after the implemented method concluded in December, that there was an improvement in fish quality by 2.97%, and an increase the sales volume and consumer satisfaction.